Dampak Penggunaan E-Commerce, Sistem Informasi Akuntansi Dan Pengetahun Akuntansi Terhadap Kinerja Usaha Kecil Menengah Di Kota Bandar Lampung - Ervita Siska Anggraini; Irawan Irawan; Endang Asliana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of the use of E-commerce, and accounting information systems and accounting knowledge, on the performance of SMEs in Bandar Lampung City with 53 respondents selected using purposive sampling techniques. Hypothesis testing was carried out using multiple linear regression analysis with the help of SPSS version 26 software. The research results showed that the use of E-commerce, accounting information systems and accounting knowledge partially had a positive and significant effect on the performance of Small and Medium Enterprises in Bandar Lampung City.